Effect of arbuscular mycorrhizal fungi and poultry manure on growth and nutrients contents of maize in different soil type - Samuel, Lihan; Rakiya, Abdullahi; Edward, R.; Demie, L. S. (Khalsa Publications, Punjab, India., 2015)
Public concerned about food safety and quality have raised interest in manipulating soil nutrients management strategies that could reduce potential threat on environment and sustain food production. Recently, the application of arbuscular mycorrhizal fungi (AMF)as bio-fertilizer has gained recognition especially, in low-input agriculture. The fungi are known to improve plant nutrition and growth. However, this effect may differ according to soil properties and nutrients concentration. A greenhouse experiment was conducted to investigate the effect of AMF and poultry manure (PM) on growth and nutrients contents in maize compared to chemical fertilizer; and to determine the effect of soil properties on colonization potential of AMF. The experiment consists of 13 treatments combinations in 2 soil types (loam and peat), viz; 6 application rates of composted PM in tones (t) ha-1 (0, 4, 6, 8, 10 and 12) and 2 levels of AMF; inoculated (+AMF) and un-inoculated (- AMF) plus recommended dose of NPK (RD NPK). Un-inoculated plants showed no symptoms of root colonization and recorded no AMF spore under both soils. Addition of PM stimulated AMF colonization and sporulation, the highest root colonization (RC %) and spore counts were recorded at 8 t PM+AMF under loam and 12 t PM+AMF in peat soils. Shoot dry biomass at 8 and 12 t PM+AMF under loam and peat were comparable to RD NPK. Applying 8 and 12 t PM+AMF in loam and peat recorded the highest N& K comparable to RD NPK. However, P content in shoot were statistically higher at 8,10 & 12 t PM+AMF in loam and at 12 t PM+AMF in peat compared to RD NPK. Application of 10 & 12 t PM+AMF in loam significantly decreased plant growth, lowered AMF RC%, and nutrient content (N & K). There was a strong positive correlation between shoot dry biomass and RC % in loam (R 2 = 0.740 P<0.01) and peat (R 2 =0.884 P<0.01). From the results of this study, it could be concluded that AMF have increased the efficiency use of PM and their integration have the potential to improve plant growth due to enhanced nutrients uptake and stimulated RC% in both soils. Results also indicated significantly higher shoot dry biomass, nutrients content (N, P, & K), spore counts and RC % in loam soil compared to peat, indicating that soil properties has a significant influence on effectiveness AMF.